Стан та управління перспективним розвитком банківської системи України - Заєць, М. А.; Zaets, Nikolay (кнту, 2014)
В статті розглядається фінансово-економічний стан та причини, які стримують розвиток банківської системи України в умовах політичної та економічної кризи. Запропоновано деякі напрямки зміцнення банківської системи, в тому числі за рахунок посилення впливу на ці процеси НБУ та розширення спектру діяльності комерційних банків. The aim of the article is to define the conditions that constrain the development of banking system and to develop the directions of its strengthening and raising the trust among population to banking system. Repeatedly the National Bank of Ukraine plays the role of observer in critical situation. It concerns abrupt fluctuations of currency rates and speculative actions of some commercial banks. The potential of the development of banking system is still essential partially due to the insufficient network of banking services. Most perspective from the point of view of profitability is a complex of services of everyday financial needs of clients. The services include payments, bills for goods and services, money saving and borrowings such as overdraft, credit cards, cash credits. The income of banking system according to the estimates for the first half-year is actually directly proportional to the level of hyena devaluation which will lead to losses of commercial banks as a result of reevaluation of short-term open currency positions and decrease of quality of currency credits services. The devaluation higher than 20% can lead to losses of all banking system.
The Condition and Management of Perspective Development of Banking System of Ukraine
Keywords: банківська система; кредитування; фінансовий моніторинг; banking system; crediting; financial monitoring